Does the sales seasonality anomaly exist in China? - Huang, Jiexiang; Tan, Yongxian; Zhao, Hailong (2020)
In this paper, we examine the relationship between sales seasonality and future stock return in the US and Chinese markets. Consistent with Grullon et al. (2020), we find low-sales-season firms tend to significantly outperform high-sales-season firms in the US market. Our empirical results suggest that the sales seasonality anomaly does not exist in the Chinese market.